Methanol‐Free Protein Expression in Komagataella phaffii With Magnetic or Non‐Magnetic Heating - Ibrahim Dagci; Seyda Yildiz Arslan; Kubra Solak; Melek Acar; Yagmur Unver; Ahmet Mavi (Microbial Biotechnology, 2025)
ABSTRACT Komagataella phaffii is among the most widely used expression systems, with methanol‐inducible promoters being preferred for protein expression due to their stringent regulation and exceptional strength. However, the applicability of this system, particularly in food and pharmaceutical products, is limited by methanol's toxic and pro‐inflammatory properties. Therefore, obtaining a novel methanol‐free expression system is necessary. In this study, we obtained a novel expression plasmid, pHSPαA, carrying the HSP70 promoter (PHSP70) to regulate heterologous expression through heat induction. The extracellular expression of azurin was achieved using this methanol‐free system under the control of PHSP70, induced by either magnetic or non‐magnetic heating. To enhance heat‐induced expression, recombinant cells were immobilised with Fe3O4@PEI25 kDa nanoparticles, which facilitated heat release under an AC magnetic field, thereby increasing cell permeability and protein secretion. A time‐dependent increase in protein expression was observed in non‐magnetic heating but not under magnetic heating. However, immobilised cells exhibited a higher protein secretion capacity compared to non‐immobilised cells. These findings suggest that the novel methanol‐free expression system represents a promising alternative for heterologous gene expression, particularly for the production of therapeutically relevant and food‐grade recombinant proteins.